Pentingnya Pengelolaan Data Refrensi dan Master Data Dalam Meningkatkan Kualitas Data Perusahaan - Lubis, Muhammad Azmi Ibadurrahman; Nasution, Muhammad Irwan Padli (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Management of reference data and master data plays a very important role in improving data quality in the corporate environment. Reference data refers to information used to provide context and definition to other operational data, while master data is the main data that is central and fundamental to various business processes. Poor data quality can negatively impact decision making, company operations, and customer satisfaction. Therefore, effective management of reference data and master data is essential in reducing duplication, increasing consistency, and ensuring data integrity across systems and departments within an organization. This study aims to analyze the challenges faced by companies in managing both types of data and how best practices in data management can improve overall data quality. The proposed approach includes implementing good data governance policies, using the right information technology tools, and establishing a solid data governance team. By ensuring structured management of reference data and master data, companies can improve operational efficiency, minimize errors, and facilitate data integration between various systems and applications used in the company. This article also explores various case studies and best practices in different industries, which can provide a concrete picture of how reference data and master data management contribute to achieving long-term business goals.